PENGARUH PENGGUNAAN BAHASA IBU DALAM KONTEKS BELAJAR MENGAJAR MATEMATIKA TERHADAP DAYA SERAP DAN MOTIVASI BELAJAR SISWA KELAS VIII SMP NEGERI 1 ROPANG TAHUN PELAJARAN 2016/2017 - Suhardin, Suhardin; Juliangkary, Eliska; Agusfianuddin, Agusfianuddin (Universitas Pendidikan Mandalika (UNDIKMA), 2017)
This study was aimed to find whether or notthe effectiveness of mother tongue have a significant effect towards students’ memory and motivation in learning mathematics at the eight students of SMP Negeri 1 Ropang. In this research, the researcher used quasy experimental research method. The population were all of the eight students at SMP Negeri 1 Ropang. the researcher divided into two classes. A class is as control group was taught by using Bahasa and B class is as experimental group was taught by using mother tongue technique. The data was obtained through pretest, posttest and laerning motivation questionnaires. The first students’ ability was seen from the result of pretest was calculated by using normality test meanwhile the last students’ ability was seen by using posttest. Before using t-test, the researcher used posttest to calculate normality test with chi-quadrate after that the researcher gave the t-test. The result of the research showed that mean score of experimental group was 42 to be 73 meanwhile control group was 25 to be 60. Therefore, the result of t-tes (0,735 )was smaller than t- table (2,017). It means that Ho was accepted and Ha was rejected. So, the researcher can concluded the effectiveness of mother tongue technique was not effective toward students’ memory and motivation in learning mathematics at the eight students of SMP Negeri 1 Ropang in academic year 2016/2017.